Towards shared unemployment insurance in the euro area - László Andor (IZA Journal of European Labor Studies, 2016)
The divergences developed within the euro area represent the main threat to the existence of the single currency and to the stability of the EU as a whole. Without proper automatic stabilisers, a monetary union can only deliver suboptimal results and may not even be sustainable. In the recent years, common unemployment insurance has been examined as one of the possible ways to improve the functioning of the Economic and Monetary Union (EMU) through automatic stabilisation. Among various options, a partial pooling of unemployment benefit schemes stands out as the model with continuous impact and direct connection with the citizens, while the political process may favour less permanent features and more conditionality. There is a strong case for connecting the EMU reform with the EU social agenda and appreciating risk-sharing in Europe from a political as well as economic point of view.
Keywords: E24; E63; F45; H12; H53; J65; 330; Arbeitslosenversicherung; Eurozone; EU-Sozialpolitik